Hemifacial Spasm Caused by Posterior Inferior Cerebellar Artery Compression due to Vertebral Artery Aneurysm: Management with Stent-Assisted Coil Embolization - Nagatsuki Tomura; Masaki Sonoda; Takashi Shuto (Neurointervention)
A 45-year-old female presented with progressive right hemifacial spasm (HFS) over 6 months. Magnetic resonance imaging revealed the right posterior inferior cerebellar artery (PICA) as the culprit vessel for HFS and a fusiform aneurysm in the vertebral artery (VA) just proximal to it. Following the patient’s request for endovascular treatment of the VA, stent-assisted coil embolization was performed to achieve PICA deviation through VA straightening after stent placement and thereby reduce HFS symptoms. At 21 months post-procedure, her HFS had resolved, with imaging confirming PICA deviation due to VA straightening, suggesting that this anatomical change contributed to symptom resolution.